2021
DOI: 10.1101/2021.07.08.451670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneous substrate binding in a glutamate transporter homologue

Abstract: Integral membrane glutamate transporters couple the concentrative substrate transport to ion gradients. There is a wealth of structural and mechanistic information about this family, including kinetic models of transport. Recent studies have revealed transport rate heterogeneity in an archaeal glutamate transporter homologue GltPh, inconsistent with simple kinetic models. The structural and mechanistic determinants of this heterogeneity remain undefined. In a mutant form of GltPh, we demonstrate substrate bind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Motivated by this paradox, we imaged TBOA-bound RSMR by cryo-EM. Following particle alignment with imposed C3 symmetry, we performed symmetry expansion and 3D classification to sort multiple conformations of the transporter protomers 34, 37 . We observed 91 % protomers in IFS with a wide-open substrate-binding site occupied by TBOA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by this paradox, we imaged TBOA-bound RSMR by cryo-EM. Following particle alignment with imposed C3 symmetry, we performed symmetry expansion and 3D classification to sort multiple conformations of the transporter protomers 34, 37 . We observed 91 % protomers in IFS with a wide-open substrate-binding site occupied by TBOA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intrigued by the observation that the dominant state of TBOA-bound RSMR mutant (inward-facing S2) differs from the dominant state of the WT transporter (outward-facing S4), we imaged it by cryo-EM. Following particle alignment with imposed C3 symmetry, we performed symmetry expansion and 3D classification without alignment to sort multiple conformations of the transporter protomers in the trimer 22,23 . We observed that the dominant conformation of the RSMR mutant is an IFS with a wide-open substrate-binding site occupied by TBOA ( Figure 2a , Extended Data Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Our data suggests that the binding of Asp to Glt Ph can take place through two different pathways. A recent study of a mutant D40N/S279E and the wild-type Glt Ph transporter has also reported heterogenous Asp binding consistent with two binding modes for Asp ( 32 ). The conventional pathway consists of Na + binding to the Na1 and the Na3 sites prior to Asp binding.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study of a mutant D40N/S279E and the wild GltPh transporter has also reported heterogenous Asp binding consistent with two binding modes for Asp. (32) The conventional pathway consists of Na + binding to the Na1 and the Na3 sites prior to Asp binding. In the alternate pathway, the binding of Asp takes place after the initial binding of Na + to the Na1 site.…”
Section: Discussionmentioning
confidence: 99%